HUBUNGAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI ANAK SEKOLAH DASAR DI WILAYAH PESISIR KOTA MATARAM - LINA YUNITA; NI MADE WIASTY SUKANTY; FARIDA ARIANI (GANEC SWARA, 2023)
Nutritional problems can be in the form of macronutrient problems and micronutrient problems. One group that requires attention in consuming food and nutrients is school-aged children. School age children are children aged 6-12 years where they experience the second growth spurt after toddlerhood. School-aged children on the coast are a group that is at high risk of experiencing nutritional status problems. Adequate nutritional intake is very influential for optimal growth, development and children's health. This study aims to determine the relationship between macronutrient intake and the nutritional status of elementary school children in the coastal area of Mataram City. The method used in this research is an analytical survey with a cross sectional design and using a total sampling method. The number of samples used was 140 students in grades IV and V at SDN 18 and 38 Ampenan. Nutritional intake data was obtained through the Recall questionnaire, while nutritional status data was obtained from BMI calculations obtained from measuring height and weight. Research data was processed using the Spearman correlation test with a value of α = 0.05. The test results show the p value = 0.000. Based on these results, it can be concluded that there is a significant relationship between energy, protein, fat and carbohydrate consumption patterns and nutritional status.